THE ROLE OF OUR GREAT ANCESTORS IN THE LIFE OF OUR PEOPLE (MAHMUDXOJA BEHBUDIY’S LIFE) - Nematova Dilshoda Baxriddinova (TADQIQOTLAR.UZ, 2024)
Abstract: Everyone knows that the foundation of our new Uzbekistan, which is currently leading in every field, was not just laid, and for its development, our great grandfathers, our great teachers, the founders of modern Uzbek modernity, with their knowledge, intelligence and deep thoughtsthey made the foundations of our country so strong that they even sacrificed their lives for it. There is no one who can be a better role model for our youth, that is, the youth who are growing up today. Because to achieve a great result, to believe in our own knowledge, to be in constant search, to make the future of our country more beautiful, to make our contribution to our country, to leave no chance for mistakes, and most importantly, one big strengththey are true devotees of the country, who were able to instill in our hearts the realization that we are and that we will achieve many achievements on this path and conquer the worlds with the power of our knowledge.